Lama guanicoe remains from the Chaco ecoregion (Córdoba, Argentina): An osteological approach to the characterization of a relict wild population - Silva Ferreira Da Costa, Thiago (2018)
Guanacos (Lama guanicoe) are large ungulates that have been valued by human populations in South America since the Late Pleistocene. Even though they were very abundant until the end of the 19th century (before the high deforestation rate of the last decades), guanacos have nearly disappeared in the Gran Chaco ecoregion, with relicts and isolated populations surviving in some areas, such as the shrubland area near the saline depressions of Córdoba province, Argentina. In this report, we present the first data from a locally endangered guanaco wild population, through the study of skeletal remains recovered in La Providencia ranch. Our results showed that most of the elements belonged to adults aged between 36 and 96 months; sex evaluation showed similar numbers of males and females. Statistical analysis of the body size of modern samples from Córdoba demonstrated that guanacos from the Chaco had large dimensions and presented lower size variability than the modern and archaeological specimens in our database. Moreover, they exhibited dimensions similar to those of modern guanacos from Patagonia and San Juan, and to archaeological specimens from Ongamira and Cerro Colorado, although further genetic studies are needed to corroborate a possible phylogenetic relationship. Finally, we used archaeozoological techniques to provide a first characterization of a relict guanaco population from the Chaco ecoregion, demonstrating its value to the study of modern skeletal remains and species conservation biology.